We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
140
1
avatar+327 

Another one I need to learn better, ha-ha.

 

Is the binomial a factor of the polynomial function?

f(x)=x3+4x2−9x−36

 

Select Yes or No for each binomial.

 

Options:

 

(x-1)

(x-3)

(x+3)

(x+4)

(x-4)

 

Please and thank you! 0^>

 Nov 8, 2018
 #1
avatar+5073 
+1

\(x^3 +4x^2 -9x -36 = \\ (x^3 -9x) + 4(x^2-9) = \\ x(x^2-9)+4(x^2-9) = \\ (x+4)(x^2-9) = \\ (x+4)(x-3)(x+3)\)

.
 Nov 8, 2018

6 Online Users

avatar